PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PENGGUNA BPJS PADA RUMAH SAKIT UMUM MITRA MEDIKA AMPLAS MEDAN - Bangun, Kristina (UNIKA Santo Thomas, 2023)
The purpose of this study was to analyze the effect of the dimensions of service quality consisting of reliability, responsiveness, assurance, tangible, partial and simultaneous empathy on patient satisfaction using BPJS at the Mitra Medika Amplas General Hospital (RSU) Medan. The population of all patients using BPJS at RSU Mitra Medika Amplas Medan. A sample of 96 respondents, data collection methods through questionnaires and documentation, multiple regression analysis method. The results showed the regression equation: KP = 2.761 + 0.305K + 0.128Kt + 0.143Ky + 0.203B + 0.151E means that reliability, responsiveness, confidence, physical evidence and empathy have a positive effect on patient satisfaction. Reliability, responsiveness, confidence, tangible and Empathy has a significant simultaneous and partial effect on patient satisfaction using BPJS at RSU Mitra Medika Amplas Medan. The determinant coefficient value (R Square) is 0.514, meaning that patient satisfaction can be explained by the dimensions of service quality (Reliability, Responsiveness, Confidence, Tangibility and Empathy) of 51.4% while another 48.6% is explained by other factors not explained in this study such as security, promotion and communication. To improve the quality of service regarding reliability, it is necessary to correct all deficiencies such as the accuracy of disease diagnoses and the doctor's explanations that are not complicated, regarding responsiveness, it is necessary to improve or increase the quality of services such as the punctuality of nurses when patients need help and the speed of administrative officers in serving consumers, regarding confidence, need to improve/increase the quality of services such as confidence in the abilities and skills possessed by medical personnel, the ability of doctors to determine patient diagnoses, as well as the courtesy of staff in serving patients, regarding tangibles, need to correct all deficiencies such as waiting room facilities to equipment -examination support tools, regarding the empathy variable, need to correct any deficiencies such as doctors taking the time to listen to patient complaints, regarding patient satisfaction variables need to improve patient quality services such as Reliability, Responsiveness, Confidence, Tangible and Empathy so that with an increase in the quality of service inpatients will feel satisfied with the quality of services provided.